2023
DOI: 10.2215/cjn.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interventions Across Primary and Secondary Care to Optimize Population Kidney Health

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
(223 reference statements)
0
3
0
Order By: Relevance
“…We incorporated several components to optimize population-level value-based kidney health as identified in a recent systematic review, including automated detection of higher-risk cases, educational support, non-patient-facing nephrologist review, and dynamic integration with existing workflows. 33 Clinician learning during the process of treating patients was promoted by incorporating education in the electronic consultations. Moreover, the intervention was designed based on pilot work that demonstrated high need and receptiveness of this program among PCCs and incorporated feedback from PCCs and health system and health informatics leadership teams to ensure harmonization with PCC workflow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We incorporated several components to optimize population-level value-based kidney health as identified in a recent systematic review, including automated detection of higher-risk cases, educational support, non-patient-facing nephrologist review, and dynamic integration with existing workflows. 33 Clinician learning during the process of treating patients was promoted by incorporating education in the electronic consultations. Moreover, the intervention was designed based on pilot work that demonstrated high need and receptiveness of this program among PCCs and incorporated feedback from PCCs and health system and health informatics leadership teams to ensure harmonization with PCC workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Participating primary care practices were also heterogenous in terms of academic affiliation, geographical location, access to specialists, practice size, and use of physician extenders, thus supporting the generalizability of our findings. We incorporated several components to optimize population-level value-based kidney health as identified in a recent systematic review, including automated detection of higher-risk cases, educational support, non–patient-facing nephrologist review, and dynamic integration with existing workflows . Clinician learning during the process of treating patients was promoted by incorporating education in the electronic consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by investigators from the United Kingdom suggested that automatic identification of individuals at high risk of CKD progression and CV risk is important for improving CKD care [ 18 ]. The investigators performed a systematic review and realist synthesis to develop an integrated model of intervention mechanisms to improve the delivery of CKD care.…”
Section: Discussionmentioning
confidence: 99%